Le immagini dell' "altro" nella cronachistica del Mezzogiorno longobardo - Kujawiński, Jakub (Edizioni scientifiche italiane, 2006)
The aim of this article is to investigate how the complex political, ethnic, religious and linguistic relations in early medieval Southern Italy are reflected in the local Lombard historical writings from 9th and 10th centuries. Literary representations of four groups from outside the Lombard principalities, i.e. the Franks, the Greeks, the Arabs, and the Neapolitains, are analysed in the following texts: the “Chronica sancti Benedicti”, the “Ystoriola” by Erchempertus and the “Chronicon Salernitanum”. Lombard authors' opinions of their neighbours are mostly negative, but far from being univocal or constant. Even if 'self-image' is not treated as an autonomous topic, here it is stressed that for Lombard chroniclers talking about others was often a way to present their own group as having a particular identity, which to us appears relational to the various “others” with whom they were in contact.
Keywords: Włochy średniowieczne; Medieval Italy; Longobardowie; Lombards (people); Erchempert; Erchempertus; Chronicon Salernitanum; Chronicon Salernitanum; Etniczność; Ethnicity; Historiografia średniowieczna; Medieval Historiography; Muzułmanie; Muslims; Karolingowie; Carolingians; Bizancjum; Byzantium